Mapeamento de processos e simulação como procedimentos de apoio à gestão de custos: uma aplicação para o processo de registros e matrículas da universidade de Cruz Alta - Mareth, Taciana (Universidade do Vale do Rio do Sinos, 2008)
The theme of this dissertation consists of associating the costs management with two tools of analysis: processes mapping and simulation. In this sense, the main objective was to verify the contribution of the processes mapping and simulation as support procedures to the costs management on the registrations and enrollments of the Cruz Alta University – UNICRUZ. This was an applied and quantitative study once there was collection of data, such as service rate and students’ arrival rate, both analyzed under statistical procedures and later originated simulation models and two scenarios of each model for the final analysis. At the end of the study, it is proved the contribution of the process mapping and simulations as important support tools to the costs management, since the used methodology contributed in the improvement of the quality, in the alignment of the processes and in the costs management.
Keywords: mapeamento de processos; simulação; gestão de custos; process mapping; simulation; costs management; Ciências Sociais Aplicadas